Colonial subjects : Puerto Ricans in a global perspective - Grosfoguel, Ramón. (Berkeley : University of California Press, 2003)
Colonial Subjects is the first book to use a combination of world-system and postcolonial approaches to compare Puerto Rican migration with Caribbean migration to both the United States and Western Europe. Ramon Grosfoguel provides an alternative reading of the world-system approach to Puerto Rico's history, political economy, and urbanization processes.
Geopolitics of knowledge and coloniality of power: thinking Puerto Rico and Puerto Ricans from the colonial difference -- I: The political economy of Puerto Rico -- 1. The political economy of Puerto Rico in the twentieth century and Puerto Rican postnational strategies -- 2. World cities in the Caribbean: Miami and San Juan -- II: Puerto Rican migration and the Caribbean Diaspora in the United States -- 3. Migration and geopolitics in the greater Antilles: from the Cold War to the post-Cold War -- 4. Puerto Ricans in the United States: a comparative approach -- 5. "Coloniality of power" and racial dynamics: notes on a reinterpretation of Latino Caribbeans in New York City / with Chloe S. Georas -- III: Caribbean colonial migrants in Western Europe and the United States -- 6. Colonial Caribbean migrations to France, the Netherlands, Great Britain, and the United States -- 7. "Cultural racism" and colonial Caribbean migrants in core zones of the capitalist world-economy.
Includes bibliographical references (pages 221-242) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Puerto Ricans -- United States -- History -- 20th century; Puerto Ricans -- Migrations -- History -- 20th century; Puerto Ricans -- Europe -- History -- 20th century; Puerto Rico -- Emigration and immigration -- History -- 20th century; United States -- Emigration and immigration -- History -- 20th century; Europe -- Emigration and immigration -- History -- 20th century; Puerto Rico -- Colonial influence; Puerto Rico -- Social conditions -- 1952-; Caribbean Area -- Colonial influence; Portoricains -- Migrations -- Histoire -- 20e siècle.; Portoricains -- Europe -- Histoire -- 20e siècle.; Porto Rico -- Émigration et immigration -- Histoire -- 20e siècle.; Europe -- Émigration et immigration -- Histoire -- 20e siècle.; Porto Rico -- Influence coloniale; Porto Rico -- Conditions sociales -- 1952-; Caraïbes (Région) -- Influence coloniale; États-Unis -- Émigration et immigration -- Histoire -- 20e siècle.; 15.85 history of America; SOCIAL SCIENCE -- Emigration & Immigration; Colonial influence; Emigration and immigration; Puerto Ricans; Puerto Ricans -- Migrations; Social conditions; Caribbean Area; Europe; Puerto Rico; United States; Globalisierung; USA; Migratie (demografie); Puertoricanen; Latino-Américains -- États-Unis.; Portoricains -- États-Unis -- Émigration et immigration; Portoricains -- Europe de l'Ouest.; Porto Rico -- Emigration et immigration -- 20e siècle.; Porto Rico -- Influence coloniale; Caribbean Region -- Colonial influence; Europe -- Emigration and immigration -- History -- 20th Century; Puertoricaner; Since 1900; History